2022
DOI: 10.1155/2022/3586372
|View full text |Cite
|
Sign up to set email alerts
|

Intense ү-Ray Bursts following the Interaction of Laser Pulse with Steep Density Gradients

Abstract: We investigate the production of intense ү-rays following the interaction of ultraintense laser pulse with a hybrid combination of under-dense plasma associated with a thin foil of fully ionized Al or Cu or Au at the rear side. Relativistic electrons are accelerated following the interaction of high intensity laser pulses with an under-dense plasma. These electrons are then stopped by the thin foils attached to the rear side of the under-dense plasma. This results in the production of intense-ray bursts. So, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In this study, the polarity is identified by injecting pulse voltage into the hypothesized 􏽢 d axis. IPMSM transforms voltage and current components in the stationary coordinate system in accordance with Euler's theorem to yield the resultant vector equation [18][19][20][21][22][23][24][25], which is expressed as…”
Section: Polarity Identification By Pulse Voltage Injection Methodmentioning
confidence: 99%
“…In this study, the polarity is identified by injecting pulse voltage into the hypothesized 􏽢 d axis. IPMSM transforms voltage and current components in the stationary coordinate system in accordance with Euler's theorem to yield the resultant vector equation [18][19][20][21][22][23][24][25], which is expressed as…”
Section: Polarity Identification By Pulse Voltage Injection Methodmentioning
confidence: 99%
“…To address this challenge, various approaches involving different target structures have been proposed. These include cone targets [18], double-layer targets [19][20][21], and structured targets [22,23]. These structured targets offer advantages over planar targets by facilitating prolonged interactions between the laser and the inner volume of the target material.…”
Section: Introductionmentioning
confidence: 99%